Are mixed meat and vegetable protein products good alternatives for reducing meat consumption? A case study with burgers - Tarrega, Amparo (Curr Res Food Sci, 2020)
The principal motivations for the worldwide trend towards reducing meat consumption are health, the environment and animal welfare. The present study investigated the willingness of omnivores to introduce mixed (beef-vegetable protein) and 100% vegetable protein products into their diet. The participants (n = 251) were young adult omnivores who consumed meat at least once a week. The stimuli were images of six different products representing two beef burgers, two mixed-protein burgers (50% beef and 50% seitan or soy) and two 100% vegetable protein burgers (seitan and soy). The participants were asked to write down spontaneous associations with each product (Word Association technique) and score their expected liking and purchase intention for them. In addition, they completed a questionnaire (36 statements) to evaluate their attitude towards meat reduction, considering six aspects: diet, habits, ethics, hedonism, health, and the environment. According to their response to these statements, they were classified into three attitude groups: anti- (ANTI, n = 106), intermediate- (INTERM, n = 89), and pro- (PRO, n = 56) meat reduction. All the participants expected to like the 100% beef burger most, the PRO group expected to like all six products to a similar degree and the ANTI group expected to like the mixed product significantly more than the 100% vegetable product, indicating that the introduction of mixed proteins could be a small first step towards meat reduction for those most attached to meat. The associations elicited by the different burgers were mostly the same but were mentioned with different frequencies, which also depended on the attitude group. These distinctive association patterns showed clear connections to the motives underlying each group's attitude towards meat reduction. It may be concluded that mixed products would be a reliable although timid option for consumers who are attached to meat to reduce their meat intake, while any of the products containing vegetable proteins would be an option for consumers who are more favourable towards meat reduction.